Conciliatory Anti-Allergic Decoction Attenuates Pyroptosis in RSV-Infected Asthmatic Mice and Lipopolysaccharide (LPS)-Induced 16HBE Cells by Inhibiting TLR3/NLRP3/NF-κB/IRF3 Signaling Pathway - Ya-qin Chen; Yan Zhou; Qi-li Wang; Jian Chen; Hua Chen; Hui-hui Xie; Lan Li (Journal of Immunology Research)
Respiratory syncytial virus (RSV) infection can deteriorate asthma by inducing persistent airway inflammation. Increasing evidence elucidated that pyroptosis plays a pivotal role in asthma. Conciliatory anti-allergic decoction (CAD) exhibits an anti-inflammatory effect in ovalbumin (OVA)-induced asthma; however, the effects and mechanisms of CAD in RSV-infected asthmatic mice have not yet been elucidated. The RSV-infected asthmatic mice model and lipopolysaccharide (LPS)-induced 16HBE cell pyroptosis model were established, respectively. Pulmonary function, ELISA, and histopathologic analysis were performed to assess the airway inflammation and remodeling in mice with CAD treatment. Furthermore, ultra-performance liquid chromatography-quadrupole time-of-flight/mass spectrometry (UPLC-Q-TOF/MS) was conducted to identify the chemical compounds of high-dose CAD (30 g/kg). Cell viability and apoptosis of 16HBE cells were assessed by CCK-8 and flow cytometry assays, respectively. Finally, the expression levels of apoptosis-, pyroptosis-, and TLR3/NLRP3/NF-κB/IRF3 signaling-related genes were measured with qRT-PCR or western blotting, respectively. Pulmonary function tests showed that CAD significantly ameliorated respiratory dysfunction, airway hyperresponsiveness, inflammation cell recruitment in BALF, pulmonary inflammation, collagen deposition, and cell death in lung tissues. CAD significantly decreased the content of TNF-α, IL-13, IL-4, IL-1β and IL-5 in the bronchoalveolar lavage fluid (BALF), IL-17, IL-6, and OVA-specific IgE in serum and increased serum IFN-γ in asthma mice. The results of UPLC-Q-TOF/MS showed that high-dose CAD had 88 kinds of chemical components. In vitro, CAD-contained serum significantly suppressed LPS-induced 16HBE cell apoptosis. Additionally, CAD and CAD-contained serum attenuated the up-regulated expressions of Bax, Cleaved caspase-3, NLRP3, ASC, Cleaved caspase-1, GSDMD-N, IL-18, IL-1β, TLR3, p-P65, p-IκBα, and IRF3 but increased Bcl-1 and GSDMD levels in the asthma mice and LPS-induced 16HBE cells, respectively. These results illustrated that CAD may have a potential role in improving airway inflammation and pyroptosis through inhibition of the TLR3/NLRP3/NF-κB/IRF3 signaling pathway.